STRATEGI PELESTARIAN TANAMAN OBAT DALAM PERSPEKTIF BUDAYA - Adiputra, I Nyoman; Indah Sri Handari A., Luh Made (Bumi Lestari, 2012)
The traditional medicine still exists in Bali; it is supported by the fact that some plants are used for traditional drugs. Up now, the Balinese traditional medicine still functions. It is as an element of Balinese culture. As a consequence of development in general, there is a shift in land-use. It is assumed, that some of medicinal plants will exctinctive. It is a fact; the young generation is not familiar with the medicinal plants. Not all of the medicinal plants have been studied, its effect as well its active compound. Eventually, there is a trend in Balinese society, that they are favor of horticulture, by making use of medicinal plants. That is become a stepping stone for conservation of the medicinal plants. In relation to that, a walk-through survey was conducted in 20 households, 26 out of house yards, 10 governmental offices, 10 stars hotels, and five segments of median road in Denpasar. The goals are: to know the total number of horticultures planted, kind of the medicinal plants used as horticultures. The results found are as follows: 1) there are about 190 names of plants for horticultures; 2) many of the medicinal plants are used for the horticultures; 3) the horticultures are planted in house yards, out of house yards, government offices stars hotels and median road; 4) through horticultures some of the scarcely medicinal plants could be preserved. The conclusions could be drawn are: 1) the horticultures make use of local existing-medicinal plants; 2) for horticultures it is also imported from other islands; and 3) the horticultures could be used as a strategy for medicinal plants conservation in Bali. For further study the followings suggestions are addressed: a) all of the medicinal plants in Bali used for horticultures; b) more attempt must be focused on the existence of medicinal plants in Bali; c) the idea for establishing medicinal plants park in Bali, needs support from all stake holders, for natural resources conservation and preservation. The preserved medicinal plants will be good as an asset for education, tourism and social-cultural aspect as well.
Keywords: medicinal plants, horticultures, consevation, preservation